Factibilidad para exportación de la quinua orgánica hacia el mercado japonés - Illicachi Gualli, William Roberto (2014)
Ecuador's export supply is heavily concentrated in non-renewable natural resources and commodities, which are exported as inputs to be processed and incorporated into final goods outside the national economic sphere or for final consumption, being mostly in the case of consumer goods perishable. The PREE (Popular Radio Schools of Ecuador, have managed to train 245 farmers from indigenous communities in Chimborazo and Bolivar, about growing organic quinoa, project operating since 1998 and has exported its products to USA and Europe great reception. however in recent years have failed to locate all of its production, with an average surplus of 200 tonnes per year quinoa…..